'I waste food but this is not my fault!': Exploring the drivers of plate waste in foodservices of Turkey through the prism of neutralisation theory. (20th December 2021) - Coşkun, Ayşen; Filimonau, Viachaslau
Abstract: Plate leftovers account for a substantial portion of food waste generated in foodservices. Although consumers acknowledge this wastage, they blame others or circumstances beyond their control for why plate leftovers occur, thus showcasing deviant behaviour. This study advocates that neutralisation theory can aid in understanding the antecedents of this deviance. The study employs modified theory of planned behaviour to test the role of selected neutralisation techniques in the context of the hospitality and foodservice of Turkey, an established market of out-of-home food consumption. The findings show that denial of responsibility and appeal to higher loyalties, as the key neutralisers, predict wasteful consumer behaviour. Knowledge of food waste and personal attitudes can reduce the impact of these neutralisation techniques, but cannot eliminate it entirely. To tackle plate leftovers, industry practitioners, policy-makers and academics should identify effective counter measures against customer deviance driven by neutralisation. Financial (dis)incentives, (re) design of business operations and more flexibility given to consumers when placing food orders may represent such counter measures. Highlights: Neutralisation theory can aid in explaining why restaurant guests leave meals uneaten. Denial of responsibility and appeal to higher loyalties predict plate waste. Food waste knowledge and moral norms do not predict intention to reduce leftovers. Both can however reduce the negative effect of appeal to higher loyalties. Financial (dis)incentives and operational (re-)design can aid in counteracting the neutralisers.